Towards intercultural communication effectiveness (congruence) in Sino-African interactions - Fungai Chigwendere; Lynette Louw (Communicare)
Within the field of intercultural communication, the position of theorist is adopted, to re-think and reframe existing insights by creatively combining them in a more useful and holistic way, towards intercultural communication effectiveness (congruence). More specifically, this paper is premised on the view that intercultural communication awareness resulting from an understanding of communication cultures of those in interaction can enable development of appropriate strategies for enhancing intercultural communication effectiveness (ICE). Thus, with reference to the Sino-African cultural context, a synthesis of literature on culture and communication in Western, African, and Chinese cultures on the basis of a conceptual framework for intercultural communication effectiveness is conducted. The result is a framework reflecting potential synergies and differences in communication culture and patterns, while also suggesting low culture distance between African and Chinese culture. A higher culture distance is reported when African and Chinese cultures are compared to Western cultures. Patterns of similarity and difference in African and Chinese communication culture are also presented. This paper contributes to the limited knowledge of intercultural communication in Sino-African interactions by providing insights into African communication culture and comparing three cultures (Chinese, African, and Western).